ENSO and Pacific Decadal Variability in the Community Earth System Model Version 2. (18th December 2020) - Capotondi, A.; Deser, C.; Phillips, A. S.; Okumura, Y.; Larson, S. M.
Abstract: This study presents a description of the El Niño–Southern Oscillation (ENSO) and Pacific Decadal Variability (PDV) in a multicentury preindustrial simulation of the Community Earth System Model Version 2 (CESM2). The model simulates several aspects of ENSO relatively well, including dominant timescale, tropical and extratropical precursors, composite evolution of El Niño and La Niña events, and ENSO teleconnections. The good model representation of ENSO spectral characteristics is consistent with the spatial pattern of the anomalous equatorial zonal wind stress in the model, which results in the correct adjustment timescale of the equatorial thermocline according to the delayed/recharge oscillator paradigms, as also reflected in the realistic time evolution of the equatorial Warm Water Volume. PDV in the model exhibits a pattern that is very similar to the observed, with realistic tropical and South Pacific signatures which were much weaker in some of the CESM2 predecessor models. The tropical component of PDV also shows an association with ENSO decadal modulation which is similar to that found in observations. However, the ENSO amplitude is about 30% larger than observed in the preindustrial CESM2 simulation, and even larger in the historical ensemble, perhaps as a result of anthropogenic influences. In contrast to observations, the largest variability is found in the central Pacific rather than in the eastern Pacific, a discrepancy that somewhat hinders the model's ability to represent a full diversity in El Niño spatial patterns and appears to be associated with an unrealistic confinement of the precipitation anomalies to the western Pacific. Plain Language Summary: The Community Earth System Model Version 2 (CESM2) is the latest version of the Earth System models developed at the National Center for Atmospheric Research in Boulder, CO. This study examines how well CESM2 simulates the El Niño–Southern Oscillation (ENSO), the leading mode of climate variability in the tropical Pacific at interannual timescales, with a large influence on the global climate and very important societal impacts. The modeled ENSO exhibits a larger amplitude than observed, with anomalies displaced further west than in observations, but with dominant timescale, temporal evolution, precursors, and teleconnections in good agreement with observations. This study also examines the model performance in simulating climate variability at decadal timescales in the Pacific sector. The spatial pattern of Pacific Decadal Variability and the relationship between decadal variations in the tropical Pacific and decadal ENSO modulation are well simulated by CESM2. Key Points: El Niño–Southern Oscillation in the model exhibits realistic timescale, precursors, temporal evolution, and teleconnections The El Niño–Southern Oscillation amplitude is about 30% larger than observed, with anomalies displaced too far west than observed The model Pacific Decadal Variability has a realistic spatial pattern